The Political Economy of Financial Reforms in Cameroon - Neba Cletus Yah (Jurnal Ekonomi dan Studi Pembangunan, 2020)
The aim of this study is to analyse the factors that influence the adoption of financial sector reforms in Cameroon. The Abiad et al. (2008) technique is used to construct a financial reform index for Cameroon and the ordered logit model employed to identify its drivers for the period 1973-2017. The results show that financial reforms in Cameroon follow a progressive and constant pace and stands at the level of 88% in relative terms in 2017. The process of financial reforms is driven by the level of financial development, institutional quality, trade openness and economic crisis.